Global community should learn the Malay language – James T.Collins - UMP, PNC
For the first time, Universiti Malaysia Pahang (UMP)’s Centre for Modern Languages & Human Sciences (CMLHS) organised a public lecture titled, ‘Lexicography, Dictionary and Online Dictionary’ delivered by Professor James T. Collins.